2021
DOI: 10.3390/ijerph18105481
|View full text |Cite
|
Sign up to set email alerts
|

‘All We Have to Decide Is What to Do with the Time That Is Given to Us’ a Photovoice Study on Physical Activity in Nursing Homes

Abstract: (1) Background: Despite high prevalence of physical inactivity and sedentariness among nursing home residents, research on the influence of environments on this topic remains scarce. This Photovoice study explores how structural and social environments relate to residents’ everyday physical activity (PA). (2) Methods: 27 residents, staff, and significant others conducted Photovoice in eight nursing homes in Germany to document factors facilitating or hindering PA. Photographs were discussed with the participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…In our sub-study, we used multi-sited focused ethnography to identify distinctive perspectives and experiences of specific actor groups (Knoblauch, 2005) to examine potential and challenges of Photovoice as a method to study PA promotion in nursing homes. We present our findings from the larger Photovoice project involving barriers and options for PA promotion elsewhere (Altmeier et al, 2021).…”
Section: Our Case Study Project On Physical Activity Promotion In Nur...mentioning
confidence: 99%
See 1 more Smart Citation
“…In our sub-study, we used multi-sited focused ethnography to identify distinctive perspectives and experiences of specific actor groups (Knoblauch, 2005) to examine potential and challenges of Photovoice as a method to study PA promotion in nursing homes. We present our findings from the larger Photovoice project involving barriers and options for PA promotion elsewhere (Altmeier et al, 2021).…”
Section: Our Case Study Project On Physical Activity Promotion In Nur...mentioning
confidence: 99%
“…Two co-authors conducted the fieldwork and combined data from the original Photovoice study (Altmeier et al, 2021), field observations, and formal observations and informal interviews during Photovoice, totaling 42 observation hours in eight nursing homes from February 2020-November 2020. In addition to observations during the Photovoice study, we observed PA patterns and interactions and organizational structure and culture for 200 hours over 34 days between January and February 2020 in the eight nursing homes during our fieldwork.…”
Section: Data Collection Processmentioning
confidence: 99%
“…There is a considerable need for interventions that are based on or take into account the needs of IWD, and also assist or train nurses on how to promote and deliver a physical activity program. This was concluded by Altmeier et al (2021) who conducted a photovoice study on physical activity in eight nursing homes in Germany. To this end, Information and Communication Technology (ICT) may have the potential to address the requirements of both IWD and nursing home employees in order to mitigate the negative effects of the pandemic, and also to sustainably modify the everyday life of IWD in nursing homes.…”
Section: Introductionmentioning
confidence: 99%
“…In view of the COVID-19 restrictions, the following two main aspects were addressed in the present study where we aimed at developing an ICT-based solution to tackle physical inactivity in nursing homes: The first was to satisfy the different stakeholder groups, e.g., nursing home assistants, nursing home leadership, etc. (Altmeier et al, 2021). The second was to follow a pragmatic and ecological approach and consider the limited resources of health care institutions such as nursing homes (Aubertin-Leheudre and Rolland 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Since its introduction through Wang and Burris ( 23 ), Photovoice has been used in health promotion to explore the views of different vulnerable groups. These include, for example, children and youth ( 24 ), people with disabilities ( 26 ), homeless people ( 27 ), residents of nursing homes ( 28 ), and women in specific life situations such as low-income, single-parent, immigrant backgrounds, and so forth ( 29 , 30 ). In promoting PA, Photovoice was mainly used with children and adolescents, people with disabilities, and older people to investigate their attitudes, opinions, and factors that may hinder or promote their PA.…”
Section: Introductionmentioning
confidence: 99%